An immigrant neighborhood : interethnic and interracial encounters in New York before 1930 - Yee, Shirley J., 1959- (Temple University Press, 2012)
Examining race and ethnic relations through an intersectional lens, Shirley Yee's An Immigrant Neighborhoodinvestigates the ways that race, class, and gender together shaped concepts of integration and assimilation as well as whiteness and citizenship in lower Manhattan during the late nineteenth and early twentieth-centuries. In contrast to accounts of insulated neighborhoods and ethnic enclaves, Yee unearths the story of working class urban dwellers of various ethnic groups-Chinese, Jews, Italians, and Irish-routinely interacting in social and economic settings.<P.